Contrasting P-T conditions recorded in ultramafic high-pressure rocks from the Variscan Schwarzwald (F.R.G.) - Kalt, Angelika; Altherr, Rainer; Hanel, Michael (Contributions to mineralogy and petrology, 1995)
This paper presents mineralogical and tex-tural data as well as thermobarometric calculations on ultramafic high-pressure rocks from the Variscan basement of the Schwarzwald (F.R.G.). The rocks form small isolated bodies within low-pressure / high-temperature gneisses and migmatites. The results of this study constrain contrasting P-T evolutions for four garnet-bearing ultramafic high-pressure rocks. Two magnesian garnet-spinal peridotites sampled near the southern margin of the Central Schwarzwald Gneiss Complex (CSGC) were equilibrated at 670-740° C and 1.4-1.8 GPa. These P-T conditions are similar to those recorded by eclogites intercalated in the same basement unit. Two garnet websterites sampled from the northern part of the CSGC have comparatively low Mg/(Mg + Fe) and low Cr and Ni abundances and are interpreted as former cumulates. These rocks most probably experienced an initial high-temperature stage within the spinel peridotite stability field, followed by re-equilibration at 740-850° C/3.2-4.3 GPa and subsequent recrystallization at lower pressures. Further petrologic studies have to reveal whether ultramafic high-pressure rocks of the Schwarzwald can generally be assigned to these two groups which are mainly defined by contrasting peak pressures.
Gesehen am 10.01.2023